FACTORS RELATED TO RESILIENCE IN TYPE 2 DIABETES MELLITUS PATIENTS IN DENPASAR BASED ON SELF-CONCEPT MODE OF ROY ADAPTATION MODEL - Ni Made Candra Yundarini; Noorhamdani Noorhamdani; Heri Kristianto (Belitung Nursing Journal, 2018)
Background: Patients with type 2 Diabetes mellitus are impaired both physically and psychologically. Based on preliminary studies carried out in public health centers in Denpasar, Bali, out of 10 patients interviewed, 70% of the patients with type 2 diabetes mellitus expressed their difficulties in adapting to the current state of the disease. One of the capabilities that must be owned by the patients to be able to adapt to the stressor is resilience. Roy adaptation model could be used in order to explain factors associated with resilience in patients with type 2 diabetes mellitus. Objective: To analyze the factors associated with resilience in patients with type 2 diabetes mellitus in Denpasar based on self-concept mode of Roy adaptation model. Methods: It used an observational analytic design with cross-sectional approach. Respondents used in this study were type 2 diabetes mellitus patients in four selected public health centers in Denpasar, Bali. 125 samples obtained by cluster sampling technique were used in this study. Conor-Davidson Resilience Scale-2 (CD-RISC-2), Illness Identity Questionnaire (IIQ) and Functional Assessment of Chronic Illness Therapy-Spiritual Well-being (FACIT-Sp) questionnaires were used in order to measure resilience, self-concept, and spirituality respectively. Pearson Product Moment test was used for bivariate analysis to determine the relationship between self-concept and spirituality and resilience in patients with type 2 diabetes mellitus. Multiple Linear Regression was used for multivariate analysis in order to find the most dominant factor related to resilience based on self-concept mode of Roy adaptation model. Results: The results of this study showed a significant relationship between self-concept and spirituality with resilience in patients with type 2 diabetes mellitus (p = 0.000). These two variables have r values equal to 0.599 and 0.597 respectively. Multiple linear regression showed that self-concept was the dominant factor related to resilience based on self-concept mode of Roy adaptation model with beta value equals to 0.687. Conclusion: There was a significant relationship between factors associated with resilience in patients with type 2 diabetes mellitus in Denpasar based on self-concept mode of Roy adaptation model.